2019
DOI: 10.1093/auk/ukz054
|View full text |Cite
|
Sign up to set email alerts
|

Biotic interactions are the dominant drivers of phylogenetic and functional structure in bird communities along a tropical elevational gradient

Abstract: Understanding how biotic and abiotic interactions influence community assembly and composition is a fundamental goal in community ecology. Addressing this issue is particularly tractable along elevational gradients in tropical mountains that feature substantial abiotic gradients and rates of species turnover. We examined elevational patterns of avian community structure on 2 mountains in Malaysian Borneo to assess changes in the relative strength of biotic interactions and abiotic constraints. In particular, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 74 publications
8
28
2
Order By: Relevance
“…Interestingly, though, our results mesh well with inferences from studies of phylogenetic community structure. These studies of the degree to which species in communities are phylogenetically related indicate that competition is more important at low elevations, whereas physiological constraints, either direct or indirect, are more important at high elevations (Boyce et al, ; Graham, Parra, Rahbek, & McGuire, ; Machac, Janda, Dunn, & Sanders, ). Our results provide a complementary test of these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, though, our results mesh well with inferences from studies of phylogenetic community structure. These studies of the degree to which species in communities are phylogenetically related indicate that competition is more important at low elevations, whereas physiological constraints, either direct or indirect, are more important at high elevations (Boyce et al, ; Graham, Parra, Rahbek, & McGuire, ; Machac, Janda, Dunn, & Sanders, ). Our results provide a complementary test of these results.…”
Section: Discussionmentioning
confidence: 99%
“…To test for possible phylogenetic signal in the direction and magnitude of species range shift values, we used a maximum likelihood tree of Bornean birds based on a concatenated dataset of two mitochondrial and two nuclear loci from Boyce, Shakya, Sheldon, Moyle, and Martin () and package ‘phylosignal’ (Keck, Rimet, Bouchez, & Franc, ) to calculate Moran's I for each pair of mountains. Moran's I is a measure of autocorrelation of traits along the tree (Gittleman & Kot, ).…”
Section: Methodsmentioning
confidence: 99%
“…Along an elevation gradient, temperature (the variable hypothesized to explain Bergmann’s Rule) might not be the only determining factor shaping bird morphology. Indeed, in tropical mountain systems, it has been shown to be of lower importance for trait variations along elevation gradients (Freeman 2017, Boyce et al 2019); instead, flying in thin air (lower air pressure at high elevations) and the necessity to increase flight performance (due to stronger winds) might select for longer wings (Altshuler & Dudley 2006, Bears et al 2008). The seasonality of resource availability in higher elevation habitats, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Freeman (2017) found little evidence for body size clines within tropical bird species, but where there were differences, they were inconsistent with Bergmann’s Rule. Similarly, Boyce et al (2019) found that body mass of Bornean mountain birds decreased with elevation, whereas relative tarsus length increased. The authors argued that phenotypic adaptation is more likely to be driven by the foraging mode of high‐elevation species, rather than temperature (Boyce et al 2019).…”
mentioning
confidence: 83%
See 1 more Smart Citation